2013
DOI: 10.1016/j.jcrs.2012.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of corneal flap thickness in laser in situ keratomileusis using a 200 kHz femtosecond laser

Abstract: This study provides evidence of the predictability and lower variability of LASIK flaps created using the femtosecond laser. Consecutive patients having LASIK had good, predictable, and stable outcomes at the 3-month mark.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…They found that the central cap thickness accuracy was -0.7 mm and reproducibility was 4.4 mm, with 96% of eyes within 10 mm of the intended. These two studies suggest that the predictability and consistency of cap construction in SMILE is comparable to FS-LASIK flap [13,14].…”
Section: Anatomical Finding Of Smilementioning
confidence: 85%
“…They found that the central cap thickness accuracy was -0.7 mm and reproducibility was 4.4 mm, with 96% of eyes within 10 mm of the intended. These two studies suggest that the predictability and consistency of cap construction in SMILE is comparable to FS-LASIK flap [13,14].…”
Section: Anatomical Finding Of Smilementioning
confidence: 85%
“…Most recent studies [18][19][20][21][22][23][24][25][26] report the ratio of men having LASIK as 40% to 50%. Although the reasons for this discrepancy remain unclear, one possible explanation is that in the group of eyes with a long AL, including post-LASIK eyes, men tended to have cataract surgery more frequently than women, as shown in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal thickness is an important anatomical characteristic of the anterior eye and a useful indicator of corneal health, 1 a specific indicator for corneal abnormalities 2 and an essential determinant for suitability of refractive surgery. 3 An analysis, however, of the literature reporting human corneal thickness over a 30-year period indicated that a wide range of values could be encountered for nominally healthy adults and, at best, values between 473 and 595 μm would be within normal limits. 1 While some of the differences between studies can be attributed to the use of different measuring devices or different underlying optical principles, 1,4 no substantial or consistent differences in central corneal thickness in adults appeared to exist for those of Caucasian origin when age, gender or refractive error were considered.…”
mentioning
confidence: 99%